Formal models of domestic politics - Gehlbach, Scott (Cambridge : Cambridge University Press, 2013)
"A unified and accessible treatment of important formal models of domestic politics appropriate for students in political science and economics"--
Machine generated contents note: 1. Electoral competition under certainty; 2. Electoral competition under uncertainty; 3. Special interest; 4. Veto players; 5. Delegation; 6. Coalitions; 7. Political agency; 8. Regime change.
Includes bibliographical references (pages 211-222) and indexes.
Keywords: Elections -- United States -- Mathematical models; Political participation -- United States -- Mathematical models; Game theory